Relational care and co-operative endeavour – Reshaping dementia care through participatory secondary data analysis. (May 2020) - Clarke, Charlotte L; Wilcockson, Jane; Watson, Julie; Wilkinson, Heather; Keyes, Sarah; Kinnaird, Lindsay; Williamson, Toby
Dementia is emerging from the shadows of societal exclusion and stigma. The engagement within society for people who are marginalised is co-constructed through the everyday practices that take place between them and those around them. However, this is inherently political, positioning people as active and activist in the relationship of their lives with their communities. The research aimed to interrogate an existing qualitative dataset in partnership with people living with dementia to inform the development of a way of working with people with dementia that is empowering. In this qualitative secondary data analysis project, we (1) analysed data through two theoretical lenses: Douglas' cultural theory of risk and Tronto's Ethic of Care, and (2) co-analysed the data together with people living with dementia during 16 workshops. The design involved cycles of presenting, interpreting, representing and reinterpreting the data and findings between multiple stakeholders. We identified a granular understanding of the way relationships change for people with dementia and how subtle factors and nuanced behaviour contribute to social exclusion, or support social inclusion. The results support relational care through the co-operative endeavour (of co-operative communication, co-operative action and co-operative care) in promoting the inclusion of people living with dementia.